FRI0755-HPR Potential benefits of biologics on cardiovascular diseases and orthopedic surgeries in patients with rheumatoid arthritis: a nationwide population-based cohort study in taiwan. (15th June 2017) - Chen, D-Y; Tang, C-H; Yu, F; Huang, C-Y
Abstract : Background: Rheumatoid arthritis (RA) is a chronic, systemic inflammatory disorder, precipitating chronic inflammation of the joints, and also affects organs throughout the body, and even results in joint deterioration/disability. RA-related inflammation that is responsible for synovial lesions may be implicated in the development of accelerated atherosclerosis, leading to increased risk of cardiovascular disease (CVD), and increased mortality. Objectives: This study aimed at examining changes in the risk of deaths, CVD and RA-related orthopedic surgeries between the patients treated with conventional synthetic and biologic disease modifying antirheumatic drugs (csDMARD and bDMARD) for RA during 1997–2011. Methods: Two cohorts of severe RA patients and their matched controls were identified from National Health Insurance claims database. The csDMARD cohort was patients who had medication claim for cyclosporine ≥50 mg/day with concomitant use of ≥2 csDMARDs for ≥28 days within 56 days after cyclosporine use during 1997–2003 (N=1, 569). After csDMARD cohort was determined, the bDMARD cohort was selected if patients had ≥1 claim for bDMARD during 2003–2011 (N=1, 530). Adjusted hazard ratios (aHRs) for the risk of death, myocardial infarction (MI), stroke, and RA-related orthopedic surgeries were assessed between the two cohorts and their controls, respectively, using Kaplan-Meier survival curves and Cox proportional hazards models. Results: RA patients using bDMARD showed a markedly decreased risk of death (aHR:1.05; 95% CIs=0.84–1.33) compared with RA patients using csDMARD (aHR:8.75; CIs=7.43–10.31). Also, bDMARD was associated with a reduced risk of stroke (aHR:0.37; CIs=0.22–0.62) compared with csDMARD (aHR:0.73; CIs=0.51–1.05). For RA-related orthopedic surgeries, risks were slightly lower for bDMARD (aHR:4.14; CIs=3.30–5.20) compared with csMARD (aHR:5.77;CIs=4.88–6.81). Conclusions: The introduction of biologics in the treatment of RA has showed to have beneficial impact on improving clinical outcomes, including decreased risks of death, stroke and RA-related orthopedic surgeries. References: Avina-Zubieta JA, et al. Ann Rheum Dis. 2012 Sep;71(9):1524–1529. Maradit-Kremers H, et al. Arthritis Rheum. 2005 Feb;52(2):402–411. Acknowledgements: NA. Disclosure of Interest: D.-Y. Chen: None declared, C.-H. Tang: None declared, F. Yu Employee of: Pfizer Ltd., C.-Y. Huang: None declared